Total neoadjuvant therapy for rectal cancer: evidence and challenge - Suk-Hwan Lee (Annals of Coloproctology, 2023)
Recent advances in the management of rectal cancer have dramatically changed the clinical practice of colorectal surgeons because the main focus of rectal cancer treatment has changed from sphincter-saving to an organ-preserving strategies. Modifying the delivery of systemic chemotherapy to improve patients’ survival is another progress in colorectal cancer management, known as total neoadjuvant therapy (TNT). TNT is a new strategy used by colorectal surgeons to improve the quality of life and survival of patients after treatment. TNT poses limitations or obstacles, such as overtreatment issues in patients with stage I rectal cancer. However, considering the quality-of-life issues in patients with low-lying rectal cancer necessitating a permanent colostomy, the indication for TNT will be expanded. This review summarizes the recently conducted clinical trials and foresees future perspectives on TNT.